Flow dynamics investigation of CO2/CH4 gas mixture through porous media using computational approach - Qasim, A. (Trans Tech Publications Ltd, 2014)
The following study involves the investigation of hydrodynamics inside the packed column both at laboratory scale which is HPVA high pressure adsorption analyzer chamber and pilot scale. The simulations are performed in ANSYS FLUENT14. Velocity variation due to porous media along with the pressure gradient for different adsorbent particle sizes and varying flow rates are obtained and compared for both the scales. Simulation is based on the criterion which identifies the emergence of non-Darcy flow. Â© 2014 Trans Tech Publications, Switzerland.